Coordination compounds of some transition metal ions with new Schiff base ligand derived from dibenzoyl methane. Structural characterization, thermal behavior, molecular structure, antimicrobial, anticancer activity and molecular docking studies. (29th September 2017) - Mahmoud, Walaa H.; Mohamed, Gehad G.; El‐Sayed, Omnia Y.
Abstract : Series of Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) complexes were prepared with tetradentate Schiff base ligand derived by condensation of 2‐aminophenol with dibenzoylmethane. The novel Schiff base H2 L (2–2′‐((1Z, 1Z')‐(1, 3‐diphenyl propane‐1, 3 diylidene) bis (azanylylidene) diphenol) and its binary metal complexes were characterized by physicochemical procedures i.e. elemental analysis, FT‐IR, UV–Vis, thermal analyses (TGA/DTG), mass spectrometry, magnetic susceptibility and conductometric measurements. On the basis of these studies, an octahedral geometry for all these complexes was proposed expect Ni(II) complex which had tetrahedral geometry. Molar conductivity values revealed that the complexes were electrolytes except Mn(II), Zn(II) and Cd(II) complexes were non electrolytes. The ligand bound to the metal ions via two azomethine N and two phenolic OH as indicated from the IR and 1 H NMR spectral study. The molecular and electronic structures of H2 L and its zinc complex were optimized theoretically and the quantum chemical parameters were calculated. The antimicrobial activity against a number of bacterial organisms as Streptococcus pneumonia, Bacillus Subtilis, Pseudomonas aeruginosa and Escherichia coli and fungi as Aspergillus fumigates, Syncephalastrum racemosum, Geotricum candidum and Candida albicans by disk diffusion method were screened for the Schiff base and its complexes. The Cd(II) complex has potent antimicrobial activity. Anticancer activity of the Schiff base ligand and its metal complexes were evaluated in human cancer (MCF‐7 cells viability). The Cr(III) complex exhibited higher activity than other complexes and ligand. Molecular docking was used to predict the binding between Schiff base ligand (H2 L) and its Zn(II) complex and the receptors of RNA of amikacin antibiotic (4P20) and human‐DNA‐Topo I complex (1SC7). The docking study provided useful structural information for inhibition studies. Abstract : Novel Schiff base H2 L and its binary metal complexes were characterized by standard physicochemical procedures. The molecular and electronic structures of H2 L and its zinc(II) complex were optimized theoretically and the quantum chemical parameters were calculated. The Cd(II) complex has potent antimicrobial activity than the Schiff base and remaining complexes. The Cr(III) complex exhibited higher anticancer activity than other complexes and ligand. Molecular docking study provided useful structural information for inhibition studies.